(3GdCTQGa Ydi eYQaI GdCWQGas - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s ((3EHQGgje Hf CMeO Hf EHQGgje GdcfGfi GdYSbdGfi s)
(3ChdgG (B:s
(3Yf eMeO Hf jhSa MOjK Cf GdfHi Udi Gddg Ydjg hSde cGf jHOC EPG CNWQ HGdJeQ s
(3BNQgG (B:s
(3MOjK ef bGd GSJZaQ Gddg GdPi dG Edg EdG gh GdMi Gdbjhe GdMOjK s
(3eLdO jJVef ef eSGfjO MQa GdgeRI Edi eSGfjO MQa GdRjf GdeLdO fGbU GdLRA GdChd hLRA ef GdLRA GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs